Animovaný film - Štochlová, Helena 1949-; Vácha, Pavel, 1940-; Kozlík, Vladimír, 1953- (Praha : Odeon, 1985)
Katalóg výstavy venovanej výnimočným tvorcom českého animovaného filmu 2. pol. 20. storočia
Obálka Miroslav Pechánek